Pengaruh Perceived Social Media Marketing Elements terhadap Brand Awareness dan Brand Image pada Pengguna Smartphone Xiaomi di DKI Jakarta - Kurniawan, Adi; Indriyanti, Irma Satya (Media Bisnis, 2023)
This study aims to examine the impact of the influence of social media marketing elements through consumer brand engagement on brand awareness and brand image on Xiaomi smartphone users in DKI Jakarta. This study used a research design, namely descriptive research and causality research and variables were measured using seven Likert points. In taking the sample using a purposive sampling technique and using 220 respondents who fit the existing criteria. The data in this study were analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results found in this study are the influence of entertainment, EWOM and trendiness through consumer brand engagement on brand awareness and brand image among Xiaomi smartphone users in DKI Jakarta.